Ownership concentration and performance in Ukraine's privatized enterprises - Pivovarsky, Alexander (2003)
This article investigates empirically the relationship between ownership concentration and performance in 376 partially and fully privatized Ukrainian enterprises. It finds that ownership concentration is positively associated with enterprise performance in Ukraine. The article also finds that concentration of ownership by foreign companies and banks is associated with better performance than ownership concentrated by the domestic owners. Ownership by Ukrainian investment funds and holding companies does not have a positive effect on performance. The article documents that, in contrast to predictions by many observers of early transition, privatization methods determined the long-term ownership structure of privatized firms. - Reproduced.
Keywords: Public ownership - Ukraine; Public sector - Ukraine; Privatization